Determination of Rate of Release of Dye from the Hydrogels using Spectrophotometer Studies - Iqubal, Dr. S. M. Shakeel (Asian Journal of Pharmaceutics (AJP), 2020)
Introduction: The main aim of the research was to determine the rate of release of dye from the hydrogels using spectrophotometer studies. Materials and Methods: The gelatin (GE)-polyethylene glycol (PEG) composite hydrogels were prepared by the simultaneous method. Several combinations of GE-PEG composite hydrogels were prepared with methylene blue (MB) dye in it. The components were thoroughly mixed by stirring the solution during preparation to make them homogeneous. Results and Discussion: The effects of glutaraldehyde, GE, and PEG variation on dye release with different hydrogel composition samples investigated. The results showed that as the concentration of cross-linking agent increases from 5 ml to 15 ml, absorbance of the sample decreased from 0.43 to 0.42 in demineralized water and 0.47 to 0.42 in 0.1M HCl due to decrease in the pore diameter of the sample, and with increased GE composition from 2.0 g to 4.0 g, absorbance of the sample also increased. Conclusion: The increased amount of GE decreased the intactness of the matrix, allowing the greater release of MB. The hydrophilic nature of PEG increases the interaction with the solvent which causes swelling of the microvoids, thus resulting in the high release of MB.